STUDY MIXED METHODS PPNMSS (PERCEIVED PRENATAL MATERNAL STRESS SCALE) TERHADAP TINGKAT STRES IBU REMAJA DENGAN KTD (KEHAMILAN TIDAK DIINGINKAN) - Risatantry Gultom; Wellina Br Sebayang; Hotmauli Sitanggang (Jurnal Ilmiah Kebidanan Imelda, 2024)
Teenage pregnancy is a global phenomenon with well-known causes and serious health, social and economic impacts. Globally, the Adolescent Birth Rate (ABR) is decreasing, but the rate of change is uneven across regions. Adolescent mothers (aged 10–19 years) face a higher risk of eclampsia, puerperal endometritis, and systemic infections than women aged 20–24 years, and infants of adolescent mothers face a higher risk of low birth weight, preterm birth, and neonatal emergencies. The purpose of this study was to analyze and explore the stress levels of adolescent mothers with PPNMSS in unintended pregnancies. The research method used was a mixed method with a Sequential Explanatory Design approach. The sample in this study was 45 adolescent pregnant women and those who were used as qualitative research informants were adolescent pregnant women who experienced severe stress. This study used a purposive sampling technique. Data collection using the PPNMSS questionnaire and in-depth interviews. Data analysis was carried out using univariate tests with the aim of describing the characteristics of informants and the stress levels of pregnant women. In the bivariate test with the chi square test through SPSS version 25 aims to see what is related to the stress level of pregnant women who are teenagers. While qualitative analysis can be done after finding pregnant teenage mothers with the highest scores who experience stress during pregnancy. The analysis used with thematic analysis with Nvivo 12 Plus software starting from data collection, data reduction, data display, verification and confirmation of conclusions (conclusion drawing and verification). The results of the study showed that pregnant women who were teenagers were mostly 19 years old (33.0%), the majority of junior high school education (42.0%), the majority of teenage mothers did not work (80.0%) and the majority experienced severe stress (29.0%). Based on the Pearson chi-square value (0.001; 0.024; 0.029) showed a relationship between age, education and work with the stress level of pregnant women who were teenagers. The research theme consists of factors causing Unwanted Pregnancy (KTD), coping strategies for Unwanted Pregnancy, the impact of Unwanted Pregnancy. Conclusion: High stress on unwanted pregnancy and high desire among adolescent couples to have abortion, highlight the need for coping strategies and information support from health workers, especially through social media promotion.